Chlamydial Conjunctivitis - Case Series - Mirjana . A Janicijevic-Petrovic; Tatjana S. Sarenac-Vulovic; Svetlana Paunovic; Katarina M. Janicijevic; Dejan D. Vulovic; Dragan I. Vujic (Asian Journal of Medical Research, 2012)
Chlamydia trachomatis is infectious cause of eye and genital disease. Chlamydial conjunctivitis is most common cause of follicular conjunctivitis. Authors observed conjunctivitis in newborn, during labor of infected birth canal (conjunctivitis inclusoria neonatorum); pool conjunctivitis in man with urethritis (conjunctivitis inclusoria adultorum - Reiter's syndrome) and women with the pseudophakia - iatrogenic infection.Patients presented - hemosis, hyperemia, exsudation and corneal problems. Giemsa staining of conjunctival scrapings revealed cytoplasmic inclusion bodies. Conjunctival smears showed lymphocytes, mononucleares and epithelial cells. Chlamydial conjunctivitis was diagnostic by immunofluorescence assay. Positive therapeutic effects showed treatment with erithromycin and doxicycline.